Effects of Tank-Mix Adjuvants on Spray Performance Under Downwash Airflow Fields Using an Indoor Simulated UASS Spraying Platform - Supakorn Wongsuk; Yangfan Li; Zhaoyan Zhu; Mengran Yang; Hao Zhang; Li Zhang; Changling Wang; Xiongkui He (Drones)
The unmanned aerial spraying system (UASS) has emerged as an advanced tool in precision agriculture for applying plant protection products (PPP). The addition of tank-mix adjuvants to PPP solutions is a common practice to enhance aerial spray performance. However, the effects of these adjuvants on spray performance under the downwash airflow fields generated by UASS rotors remain unclear. This study aimed to evaluate the impacts of adjuvant addition (AGE852B, AGE825, AGE809, and CCL846) on droplet size spectrum and spray deposition distribution with various rotor speeds and layouts, using an indoor simulated single-rotor/multi-rotor UASS spraying platform. The results showed that adding AGE809 and AGE825 made the droplet size and distribution much better in the flat fan nozzle LU110-015 under the downwash airflow field. The spray volume fractions made with droplets smaller than 100 µm (V100) went down by 48.15% and 21.04%, respectively. Furthermore, rotor speed was found to have a significant impact on volume median diameter, relative span, and V100 (p < 0.05). The downwash airflow field was observed to increase the vertical droplet velocity, achieving a more uniform spray distribution in the central airflow area. These results show that choosing the right adjuvants and making the most of the operational parameters can improve spray deposition, coverage uniformity, and drift reduction. This gives us useful information for making PPP applications more efficient and effective in precision agriculture.